Optimal MW and MVAR control using multistage artificial immune system technique / Hairul Azuan Abdullah - Abdullah, Hairul Azuan (2009)
This project presents the development of a technique for an optimal MW and MVAR control in a power system using the Multistage Artificial Immune System (MAIS) Programming technique. The main purpose is to determine the optimal power output of generating unit so as to meet the load demand at the minimum operating cost and minimum generation losses and at the same time to improve the voltage stability while satisfying an accepted system performance under various an operating conditions. The performance of this technique is tested using the IEEE 26 buses Reliability Test System. There are three single objective functions and six multi objective functions were implemented in this project. The single objective functions are total cost of generation, minimizing the total losses and voltage improvement. For multi-objective functions, the three single objective functions have been considered and combined into six different order of optimization equation. Comparison was made in order to determine the best objective function and technique to be used in solving optimal power dispatch problem. The result shows that the proposed technique is able to determine the optimal schedule for real and reactive power generation in order to meet the objectives.